Effects of Bolus and Continuous Nasogastric Feeding on Gastric Emptying, Small Bowel Water Content, Superior Mesenteric Artery Blood Flow, and Plasma Hormone Concentrations in Healthy Adults: A Randomized Crossover Study. Issue 3 (March 2016) - Chowdhury, Abeed H.; Murray, Kathryn; Hoad, Caroline L.; Costigan, Carolyn; Marciani, Luca; Macdonald, Ian A.; Bowling, Timothy E.; Lobo, Dileep N.
Abstract : Objective: We aimed to demonstrate the effect of continuous or bolus nasogastric feeding on gastric emptying, small bowel water content, and splanchnic blood flow measured by magnetic resonance imaging (MRI) in the context of changes in plasma gastrointestinal hormone secretion. Background: Nasogastric/nasoenteral tube feeding is often complicated by diarrhea but the contribution of feeding strategy to the etiology is unclear. Methods: Twelve healthy adult male participants who underwent nasogastric intubation before a baseline MRI scan, received 400 mL of Resource Energy (Nestle) as a bolus over 5 minutes or continuously over 4 hours via pump in this randomized crossover study. Changes in gastric volume, small bowel water content, and superior mesenteric artery blood flow and velocity were measured over 4 hours using MRI and blood glucose and plasma concentrations of insulin, peptide YY, and ghrelin were assayed every 30 minutes. Results: Bolus nasogastric feeding led to significant elevations in gastric volume ( P < 0.0001), superior mesenteric artery blood flow ( P < 0.0001), and velocity ( P = 0.0011) compared with continuous feeding. Both types of feeding reduced small bowel water content, although there was an increase in small bowel water content with bolus feeding after 90 minutes ( P < 0.0068). Similarly, both types of feeding led to a fall in plasma ghrelin concentration although this fall was greater with bolus feeding ( P < 0.0001). Bolus feeding also led to an increase in concentrations of insulin ( P = 0.0024) and peptide YY ( P < 0.0001), not seen with continuous feeding. Conclusion: Continuous nasogastric feeding does not increase small bowel water content, thus fluid flux within the small bowel is not a major contributor to the etiology of tube feeding-related diarrhea.